Synthesis, characterization and optical properties of silver and gold nanowires embedded in mesoporous MCM-41 - Adhyapak, Parag V.; Karandikar, Prashant R.; Dadge, Jagdish W.; Aiyer, Rohini C.; Chandwadkar, Asha J. (Central European Journal of Chemistry, 2006)
Uniform nanowires of silver and gold inside the channels of MCM-41 were prepared by controlled reduction of their respective metal salts with sodium borohydride (NaBH4). Presence of nanowires of silver and gold in MCM-41 were confirmed by high angle X-ray diffraction (XRD) data (peaks between 2 theta = 30 - 60 degrees) and transmission electron microscopy (TEM) confirmed the diameter of the nanowires. Diameter of nanowires is found to be similar to 2.8 nm which is coincident with channel diameter of MCM-41. Optical properties of these heterostructured materials Ag-MCM-41 and Au-MCM-41 reveals the presence of surface plasmon absorption peaks of silver and gold respectively, and the shift in the absorption bands are associated to agglomeration of clusters inside the channels. Room temperature photoluminescence spectra exhibits interesting optical properties as observed for direct band gap semiconductors. Non-linear optical properties (NLO) corresponding to second harmonic generation (SHG) values were also recorded for self supported films of these heterostructured materials. Enhanced optical non-linearity was found to be arising from a corresponding increase of local field near the surface plasmon resonance. Further enhancement in SHG was found with poling due to an induction of orientation order. (C) Versita Warsaw and Springer-Verlag Berlin Heidelberg. All rights reserved.
Keywords: Ag/Au nanowires; MCM-41; photoluminescence; SHG; TEM

Synthesis and characterization of mesoporous carbon through inexpensive mesoporous silica as template - Karandikar, Prashant R.; Patil, K. R.; Mitra, A.; Kakade, Bhalchandra A.; Chandwadkar, Asha J. (Microporous and Mesoporous Materials, 2007)
Mesoporous silica materials have been synthesized through sol-gel reaction using inexpensive sodium silicate as source of silica and low cost hydroxy carboxylic acid compounds as templates/pore forming agents. The material measured surface area of 1014 m(2)/g, pore diameter of 65 angstrom and pore volume of 1.4 cc/g when parameters like time and temperature of synthesis along with mole ratio of TA/SiO(2) were optimized. Here TA stands for tartaric acid. Carbonization of sucrose inside the pores of above silica material at 900 degrees C followed by removal of silica framework using aqueous ethanoic solution of NaOH gave rise to mesoporous carbon material. The resulting materials were characterized by N(2)-sorption, FTIR spectroscopy, X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectroscopy, thermal analysis and cyclic voltammetry. Three dimensional interconnecting wormhole channel arrangement of mesoporous silica template leads to mesoporous carbon replica with surface area of 1200 m(2)/g. X-ray photoelectron spectroscopic study (XPS) of the mesoporous carbon material shows the concentration of carbon atom in the range of 97-98% with 1-2% oxygen and negligible amount of silica. The electrochemical double layer capacitance behavior of carbon material with the specific capacitance value of 88.0 F/g at the scan rate of 1 mV/s appears to be promising. (C) 2006 Elsevier Inc. All rights reserved.
Keywords: Electrochemical properties; hydroxy carboxylic acid; mesoporous carbon; Mesoporous silica; sodium silicate

Synthesis, characterization and catalytic study of mesoporous carbon materials prepared via mesoporous silica using non-surfactant templating agents - Pagar, Nitin S.; Karandikar, Prashant R.; Chandwadkar, Asha J.; Deshpande, Raj M. (Journal of Porous Materials, 2020)
Mesostructured silica materials with surface area in the range of similar to 700-900 m(2)/g have been prepared using hydroxy-carboxylic acid compounds such as tartaric acid, malic acid and citric acid (low cost non-surfactant template/pore forming agents) and tetraethylorthosilicate (TEOS) as silica source by sol-gel reaction. The templates were removed by either soxhlet extraction or calcination method. Mesoporous carbon molecular sieves were then prepared by carbonizing sucrose inside the pores of the above prepared mesoporous silica using sulfuric acid as a catalyst. The materials were characterized by FTIR spectroscopy, powder X-ray diffraction (XRD), N-2-sorption studies, microanalysis, thermal analysis and transmission electron microscopy (TEM). The resulting carbon material shows relatively higher surface area (similar to 1100 m(2)/g), narrow pore size distribution and pore diameter of 4-5 nm. The mesoporosity of carbon material arises from interconnecting channels arrangements of mesoporous silica template. The mesoporous carbon material was used as a support for the immobilization of rhodium complex [HRhCO(TPPTS)(3)] by ossification method. The prepared catalyst has been tested for the hydroformylation of higher olefins. The activity of the catalyst was improved by 20-30% as compared to the catalyst prepared from a conventional activated carbon support.
Keywords: Carbonization; Hydroformylation; Immobilization; Low cost templates; mesoporous carbon; Mesoporous silica